Peran Pengawasan Pemerintah Dan Badan Pengawas Obat Dan Makanan (BPOM) Dalam Peredaran Obat Palsu di Negara Indonesia (Ditinjau dari Undang-Undang Nomor 36 Tahun 2009 dan Peraturan Kepala Badan Pengurus Obat dan Makanan) - Marisca Evalina Gondokesumo; Nabbilah Amir (Faculty of Law Hang Tuah University, 2021)
Abstract Drugs play a very important role in health services because the handling and prevention of various diseases cannot be separated from the treatment with drugs. Therefore, a supervisory role is needed for the Government and the National Agency of Drug and Food Control (NADFC) to always supervise the circulation of counterfeit drugs in the community as a form of prevention. The research method used is normative juridical. The results showed that monitoring the presence of counterfeit drugs had a wide-dimensional and complex problem aspect. In order to reduce the risk as small as possible, it requires a supervisory role by the government and NADFC through regulation and standardization; safety, efficacy and quality assessments through Good Manufacturing Practices (GMP) and medicinal products before being allowed to circulate in Indonesia must obtain a distribution permit, inspection, sampling and laboratory testing of products in circulation as well as warnings to the public supported by law enforcement.